What Drives Corporate Tax Avoidance in Indonesia’s Basic Materials Sector? - Salsa Shalma Auliya; Sofie Yunida Putri (Jurnal Riset Perpajakan: Amnesty, 2026)
Tax avoidance remains a persistent challenge in emerging economies, particularly in Indonesia, where corporate tax compliance varies across industries despite continuous regulatory reforms. Empirical evidence on the effects of profitability, capital structure, and firm size on tax avoidance has produced inconsistent findings, indicating the need for further investigation. This study examines the influence of profitability, capital structure, and firm size on corporate tax avoidance among basic materials companies listed on the Indonesia Stock Exchange during 2020–2024. Tax avoidance is proxied by the Cash Effective Tax Rate (CETR), while capital intensity and financial distress are incorporated as control variables to improve model robustness. A quantitative research design was employed using balanced panel data from 38 firms, resulting in 190 firm-year observations selected through purposive sampling. Panel data regression analysis was conducted using EViews 13, with the Fixed Effect Model (FEM) identified as the most appropriate specification based on Chow and Hausman tests. The findings reveal that profitability has a significant negative effect on CETR, indicating that more profitable firms are more likely to engage in tax avoidance. Capital structure has no statistically significant influence on CETR, suggesting that leverage is not a primary determinant of corporate tax avoidance. Conversely, firm size has a significant positive effect on CETR, implying that larger firms exhibit lower tax avoidance and greater tax compliance. These findings extend agency theory by demonstrating how firm-specific characteristics shape corporate tax behavior and provide practical implications for policymakers in strengthening tax governance, regulatory oversight, and corporate compliance strategies in Indonesia's basic materials sector.